High-performance tungsten-copper composite material and preparation method thereof
By using modified carbon nanotubes with surface-loaded lanthanum and nickel in tungsten-copper composites, the problems of low density and uneven structure of existing materials are solved, and the preparation of high-performance tungsten-copper composites is realized, with excellent conductivity and mechanical properties.
Patent Information
- Application Number
- CN202411958416.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-25
AI Technical Summary
The existing tungsten copper composite preparation methods have problems such as low material density, uneven composition and structure, and low production efficiency, which are difficult to meet the needs of high-performance materials.
Modified carbon nanotubes with surface-loaded lanthanum and nickel are added to the tungsten-copper composite material, and uniform and dense WC phases and CuC phases are formed through ball milling mixing, blanking and sintering, thereby improving the conductivity and mechanical properties of the material.
It effectively improves the interface compatibility and density of tungsten-copper composite materials, improves conductivity and mechanical properties, eliminates holes, prevents abnormal growth of tungsten grains, and promotes uniform distribution of copper liquid.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of materials, and in particular to a high-performance tungsten-copper composite material and a preparation method thereof. Background Art
[0002] Tungsten copper composite materials are mainly a mixture of copper and tungsten. The melting points of tungsten and copper are very different, and the two phases are immiscible. Since tungsten copper composite materials have the high melting point of tungsten and the high conductivity of copper, at the same time, above 3000℃, copper will be evaporated and absorbed in large quantities, thereby reducing the surface temperature and electron emission of tungsten copper alloy. Therefore, tungsten copper alloy has the advantages of high conductivity, high strength and hardness, and arc erosion resistance, and has broad application prospects in many fields such as electronic packaging, aerospace, and electrode processing.
[0003] At present, traditional preparation methods such as melt infiltration and high-temperature liquid phase sintering have problems such as low material density, uneven components and structure, and low production efficiency. Therefore, the development of a new type of high-performance tungsten-copper composite material and its preparation method has important practical application value.
[0004] In view of this, this application is filed. Summary of the invention
[0005] The invention provides a high-performance tungsten-copper composite material and a preparation method thereof. The tungsten-copper alloy has excellent electrical conductivity and mechanical properties.
[0006] The present invention solves the technical problem by adopting the following technical solutions: A high-performance tungsten-copper composite material comprises the following raw materials in parts by weight: 78.5-82 parts of tungsten powder, 15-20 parts of copper powder, and 1.5-3 parts of modified carbon nanotubes; The modified carbon nanotubes are carbon nanotubes with lanthanum and nickel loaded on the surface.
[0007] The present invention creatively adds carbon nanotubes with lanthanum and nickel loaded on the surface into the tungsten-copper composite material, effectively improves the interface compatibility of tungsten and copper, has good wettability, does not agglomerate, forms more uniform and dense WC phase and CuC phase at the interface between copper and tungsten, plays an effective role in strengthening dispersion, effectively eliminates holes, improves density, and can hinder the abnormal growth of tungsten grains, facilitates the penetration and uniform distribution of copper liquid, forms a continuous copper connection phase and a lanthanum, nickel, carbon nanotube network structure, and effectively improves the electrical conductivity and mechanical properties of the composite material.
[0008] As a preferred embodiment of the present invention, the preparation method of the modified carbon nanotubes is: (1) adding multi-walled carbon nanotubes and hydrofluoric acid solution into nitric acid solution and dispersing them evenly to obtain a carbon nanotube dispersion; (2) adding dodecylphenol polyoxyethylene ether into the carbon nanotube dispersion and stirring evenly to obtain a precursor solution; (3) adding lanthanum sulfate, nickel sulfate, sodium dodecylbenzene sulfonate and a reducing agent into water and dispersing them evenly to obtain a loading liquid; (4) Dropping the loading liquid into the precursor liquid, adjusting the pH to 8.2-8.6, ultrasonically treating, and drying to obtain a precursor, and heat-treating the precursor in an oxygen atmosphere to obtain modified carbon nanotubes.
[0009] As a preferred embodiment of the present invention, the multi-walled carbon nanotubes have a diameter of 8-15 nm, a length of 30-50 μm, and a specific surface area of 210-250 m 2 / g; and / or The reducing agent is sodium sulfite.
[0010] As a preferred embodiment of the present invention, the mass fraction of the hydrofluoric acid solution is 30-40%; and / or The mass fraction of the nitric acid solution is 60-70%.
[0011] As a preferred embodiment of the present invention, the mass ratio of the multi-walled carbon nanotubes, the hydrofluoric acid solution, and the nitric acid solution is 1: (0.5-1.2): (2-5); and / or The mass ratio of the dodecylphenol polyoxyethylene ether to the carbon nanotube dispersion is (0.005-0.02):1.
[0012] As a preferred embodiment of the present invention, the mass ratio of lanthanum sulfate, nickel sulfate, sodium dodecylbenzene sulfonate, reducing agent and water is 1: (0.8-1.2): (0.01-0.03): (0.05-0.08): (4-10); and / or The mass ratio of the load liquid to the precursor liquid is (0.08~0.2):1.
[0013] As a preferred embodiment of the present invention, the temperature of the heat treatment is 120-160° C., and the time of the heat treatment is 0.5-2 h.
[0014] As a preferred embodiment of the present invention, the tungsten powder includes a first tungsten powder and a second tungsten powder, the mass ratio of the first tungsten powder to the second tungsten powder is (2-5):1; the average particle size of the first tungsten powder is 2-5 μm, and the average particle size of the second tungsten powder is 0.1-0.2 μm.
[0015] As a preferred embodiment of the present invention, the average particle size of the copper powder is 2-10 μm.
[0016] The present invention also provides a method for preparing a high-performance tungsten-copper composite material, comprising the following steps: The tungsten powder, copper powder and modified carbon nanotubes are ball-milled and mixed evenly to obtain a mixed powder, and the mixed powder is pressed and sintered to obtain a high-performance tungsten-copper composite material; The green compact has a pressure of 180-220 MPa and a holding time of 2-5 min; The sintering temperature is 1050-1120° C., and the sintering time is 2-5 hours.
[0017] The beneficial effects of the present invention are as follows: the present invention adds carbon nanotubes with lanthanum and nickel loaded on the surface into the tungsten-copper composite material, effectively improves the interface compatibility of tungsten and copper, has good wettability, does not agglomerate, forms more uniform and dense WC phase and CuC phase at the interface where copper and tungsten are combined, plays an effective role in strengthening dispersion, effectively eliminates holes, improves density, and at the same time can hinder the abnormal growth of tungsten grains, facilitates the penetration and uniform distribution of copper liquid, forms a continuous copper connection phase and a lanthanum, nickel, carbon nanotube network structure, and effectively improves the electrical conductivity and mechanical properties of the composite material. DETAILED DESCRIPTION
[0018] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0019] In the present invention, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0020] In the present invention, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0021] In the present invention, there is no particular limitation on the specific dispersion and stirring treatment methods.
[0022] The reagents or instruments used in the present invention without indicating the manufacturer are all conventional products that can be obtained commercially. The raw materials used in the comparative examples and the raw materials used in the parallel experiments of the embodiments are the same commercially available products unless otherwise specified.
[0023] Among them, the diameter of multi-walled carbon nanotubes is 8~15nm, the length is 30~50μm, and the specific surface area is 210~250m 2 / g, purchased from Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences, brand: TNIMC2.
[0024] Among them, dodecylphenol polyoxyethylene ether was purchased from Errek (Shandong) Chemical Group Co., Ltd., brand: OP-10.
[0025] Example 1 A high-performance tungsten-copper composite material comprises the following raw materials in parts by weight: 79.5 parts of tungsten powder, 18 parts of copper powder, and 2.5 parts of modified carbon nanotubes.
[0026] The tungsten powder includes a first tungsten powder and a second tungsten powder, wherein the mass ratio of the first tungsten powder to the second tungsten powder is 4:1; the average particle size of the first tungsten powder is 4 μm, and the average particle size of the second tungsten powder is 0.2 μm.
[0027] The average particle size of the copper powder is 5 μm.
[0028] The modified carbon nanotubes are carbon nanotubes with lanthanum and nickel loaded on the surface, and the preparation method of the modified carbon nanotubes is as follows: (1) adding multi-walled carbon nanotubes and a 35% by mass hydrofluoric acid solution into a 65% by mass nitric acid solution, and dispersing them uniformly at a speed of 500 rpm to obtain a carbon nanotube dispersion; the mass ratio of the multi-walled carbon nanotubes, the hydrofluoric acid solution, and the nitric acid solution is 1:1:4; (2) adding dodecylphenol polyoxyethylene ether to the carbon nanotube dispersion and stirring at a speed of 500 rpm to obtain a precursor solution; the mass ratio of dodecylphenol polyoxyethylene ether to the carbon nanotube dispersion is 0.01:1; (3) adding lanthanum sulfate, nickel sulfate, sodium dodecylbenzene sulfonate, and sodium sulfite into water and dispersing them evenly to obtain a loading liquid; the mass ratio of the lanthanum sulfate, nickel sulfate, sodium dodecylbenzene sulfonate, sodium sulfite, and water is 1:1:0.02:0.06:5; (4) Dropping the loading liquid into the precursor liquid, the mass ratio of the loading liquid to the precursor liquid is 0.15:1; adjusting the pH to 8.5 with sodium hydroxide, ultrasonically treating at 600 W for 30 min, and drying to obtain a precursor; placing the precursor in a tubular furnace, and heat treating at 150° C. for 1 h in an oxygen atmosphere to obtain modified carbon nanotubes.
[0029] The method for preparing the high-performance tungsten-copper composite material comprises the following steps: Tungsten powder, copper powder and modified carbon nanotubes were ball-milled and mixed at a speed of 600 rpm to obtain a mixed powder. The mixed powder was pressed at 200 MPa for 4 minutes and then sintered at 1100°C for 4 hours to obtain a high-performance tungsten-copper composite material.
[0030] Example 2 A high-performance tungsten-copper composite material comprises the following raw materials in parts by weight: 82 parts of tungsten powder, 15 parts of copper powder, and 3 parts of modified carbon nanotubes.
[0031] The tungsten powder includes a first tungsten powder and a second tungsten powder, wherein the mass ratio of the first tungsten powder to the second tungsten powder is 4:1; the average particle size of the first tungsten powder is 4 μm, and the average particle size of the second tungsten powder is 0.2 μm.
[0032] The average particle size of the copper powder is 5 μm.
[0033] The modified carbon nanotubes are carbon nanotubes with lanthanum and nickel loaded on the surface, and the preparation method of the modified carbon nanotubes is as follows: (1) adding multi-walled carbon nanotubes and a 35% by mass hydrofluoric acid solution into a 65% by mass nitric acid solution, and dispersing them uniformly at a speed of 500 rpm to obtain a carbon nanotube dispersion; the mass ratio of the multi-walled carbon nanotubes, the hydrofluoric acid solution, and the nitric acid solution is 1:1:4; (2) adding dodecylphenol polyoxyethylene ether to the carbon nanotube dispersion and stirring at a speed of 500 rpm to obtain a precursor solution; the mass ratio of dodecylphenol polyoxyethylene ether to the carbon nanotube dispersion is 0.01:1; (3) adding lanthanum sulfate, nickel sulfate, sodium dodecylbenzene sulfonate, and sodium sulfite into water and dispersing them evenly to obtain a loading liquid; the mass ratio of the lanthanum sulfate, nickel sulfate, sodium dodecylbenzene sulfonate, sodium sulfite, and water is 1:1:0.02:0.06:5; (4) Dropping the loading liquid into the precursor liquid, the mass ratio of the loading liquid to the precursor liquid is 0.15:1; adjusting the pH to 8.5 with sodium hydroxide, ultrasonically treating at 600 W for 30 min, and drying to obtain a precursor; placing the precursor in a tubular furnace, and heat treating at 150° C. for 1 h in an oxygen atmosphere to obtain modified carbon nanotubes.
[0034] The method for preparing the high-performance tungsten-copper composite material comprises the following steps: Tungsten powder, copper powder and modified carbon nanotubes were ball-milled and mixed at a speed of 600 rpm to obtain a mixed powder. The mixed powder was pressed at 200 MPa for 4 minutes and then sintered at 1100°C for 4 hours to obtain a high-performance tungsten-copper composite material.
[0035] Example 3 A high-performance tungsten-copper composite material comprises the following raw materials in parts by weight: 78.5 parts of tungsten powder, 20 parts of copper powder, and 1.5 parts of modified carbon nanotubes.
[0036] The tungsten powder includes a first tungsten powder and a second tungsten powder, wherein the mass ratio of the first tungsten powder to the second tungsten powder is 4:1; the average particle size of the first tungsten powder is 4 μm, and the average particle size of the second tungsten powder is 0.2 μm.
[0037] The average particle size of the copper powder is 5 μm.
[0038] The modified carbon nanotubes are carbon nanotubes with lanthanum and nickel loaded on the surface, and the preparation method of the modified carbon nanotubes is as follows: (1) adding multi-walled carbon nanotubes and a 35% by mass hydrofluoric acid solution into a 65% by mass nitric acid solution, and dispersing them uniformly at a speed of 500 rpm to obtain a carbon nanotube dispersion; the mass ratio of the multi-walled carbon nanotubes, the hydrofluoric acid solution, and the nitric acid solution is 1:1:4; (2) adding dodecylphenol polyoxyethylene ether to the carbon nanotube dispersion and stirring at a speed of 500 rpm to obtain a precursor solution; the mass ratio of dodecylphenol polyoxyethylene ether to the carbon nanotube dispersion is 0.01:1; (3) adding lanthanum sulfate, nickel sulfate, sodium dodecylbenzene sulfonate, and sodium sulfite into water and dispersing them evenly to obtain a loading liquid; the mass ratio of the lanthanum sulfate, nickel sulfate, sodium dodecylbenzene sulfonate, sodium sulfite, and water is 1:1:0.02:0.06:5; (4) Dropping the loading liquid into the precursor liquid, the mass ratio of the loading liquid to the precursor liquid is 0.15:1; adjusting the pH to 8.5 with sodium hydroxide, ultrasonically treating at 600 W for 30 min, and drying to obtain a precursor; placing the precursor in a tubular furnace, and heat treating at 150° C. for 1 h in an oxygen atmosphere to obtain modified carbon nanotubes.
[0039] The method for preparing the high-performance tungsten-copper composite material comprises the following steps: Tungsten powder, copper powder and modified carbon nanotubes were ball-milled and mixed at a speed of 600 rpm to obtain a mixed powder. The mixed powder was pressed at 200 MPa for 4 minutes and then sintered at 1100°C for 4 hours to obtain a high-performance tungsten-copper composite material.
[0040] Example 4 A high-performance tungsten-copper composite material comprises the following raw materials in parts by weight: 79.5 parts of tungsten powder, 18 parts of copper powder, and 2.5 parts of modified carbon nanotubes.
[0041] The tungsten powder includes a first tungsten powder and a second tungsten powder, wherein the mass ratio of the first tungsten powder to the second tungsten powder is 4:1; the average particle size of the first tungsten powder is 4 μm, and the average particle size of the second tungsten powder is 0.2 μm.
[0042] The average particle size of the copper powder is 5 μm.
[0043] The modified carbon nanotubes are carbon nanotubes with lanthanum and nickel loaded on the surface, and the preparation method of the modified carbon nanotubes is as follows: (1) adding multi-walled carbon nanotubes and a 30% by mass hydrofluoric acid solution into a 60% by mass nitric acid solution, and dispersing them uniformly at a speed of 500 rpm to obtain a carbon nanotube dispersion; the mass ratio of the multi-walled carbon nanotubes, the hydrofluoric acid solution, and the nitric acid solution is 1:2:2; (2) adding dodecylphenol polyoxyethylene ether to the carbon nanotube dispersion and stirring at a speed of 500 rpm to obtain a precursor solution; the mass ratio of dodecylphenol polyoxyethylene ether to the carbon nanotube dispersion is 0.005:1; (3) adding lanthanum sulfate, nickel sulfate, sodium dodecylbenzene sulfonate, and sodium sulfite into water and dispersing them evenly to obtain a loading liquid; the mass ratio of the lanthanum sulfate, nickel sulfate, sodium dodecylbenzene sulfonate, sodium sulfite, and water is 1:1:0.01:0.08:10; (4) Dropping the loading liquid into the precursor liquid, the mass ratio of the loading liquid to the precursor liquid is 0.2:1; adjusting the pH to 8.5 with sodium hydroxide, ultrasonically treating at 600 W for 30 min, and drying to obtain a precursor; placing the precursor in a tubular furnace, and heat treating at 150° C. for 1 h in an oxygen atmosphere to obtain modified carbon nanotubes.
[0044] The method for preparing the high-performance tungsten-copper composite material comprises the following steps: Tungsten powder, copper powder and modified carbon nanotubes were ball-milled and mixed at a speed of 600 rpm to obtain a mixed powder. The mixed powder was pressed at 200 MPa for 4 minutes and then sintered at 1100°C for 4 hours to obtain a high-performance tungsten-copper composite material.
[0045] Example 5 A high-performance tungsten-copper composite material comprises the following raw materials in parts by weight: 79.5 parts of tungsten powder, 18 parts of copper powder, and 2.5 parts of modified carbon nanotubes.
[0046] The tungsten powder includes a first tungsten powder and a second tungsten powder, wherein the mass ratio of the first tungsten powder to the second tungsten powder is 4:1; the average particle size of the first tungsten powder is 4 μm, and the average particle size of the second tungsten powder is 0.2 μm.
[0047] The average particle size of the copper powder is 5 μm.
[0048] The modified carbon nanotubes are carbon nanotubes with lanthanum and nickel loaded on the surface, and the preparation method of the modified carbon nanotubes is as follows: (1) adding multi-walled carbon nanotubes and a 40% by mass hydrofluoric acid solution into a 70% by mass nitric acid solution, and dispersing them uniformly at a speed of 500 rpm to obtain a carbon nanotube dispersion; the mass ratio of the multi-walled carbon nanotubes, the hydrofluoric acid solution, and the nitric acid solution is 1:0.5:5; (2) adding dodecylphenol polyoxyethylene ether to the carbon nanotube dispersion and stirring at a speed of 500 rpm to obtain a precursor solution; the mass ratio of dodecylphenol polyoxyethylene ether to the carbon nanotube dispersion is 0.02:1; (3) adding lanthanum sulfate, nickel sulfate, sodium dodecylbenzene sulfonate, and sodium sulfite into water and dispersing them evenly to obtain a loading liquid; the mass ratio of the lanthanum sulfate, nickel sulfate, sodium dodecylbenzene sulfonate, sodium sulfite, and water is 1:1:0.03:0.05:4; (4) dropping a loading liquid into a precursor liquid, wherein the mass ratio of the loading liquid to the precursor liquid is 0.08:1; adjusting the pH to 8.5 with sodium hydroxide, ultrasonically treating the precursor at 600 W for 30 min, and drying the precursor to obtain a precursor; placing the precursor in a tubular furnace, and heat treating the precursor at 150 ° C for 1 h in an oxygen atmosphere to obtain modified carbon nanotubes.
[0049] The method for preparing the high-performance tungsten-copper composite material comprises the following steps: Tungsten powder, copper powder and modified carbon nanotubes were ball-milled and mixed at a speed of 600 rpm to obtain a mixed powder. The mixed powder was pressed at 200 MPa for 4 minutes and then sintered at 1100°C for 4 hours to obtain a high-performance tungsten-copper composite material.
[0050] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that Comparative Example 1 uses multi-walled carbon nanotubes to replace modified carbon nanotubes, and the other aspects are the same.
[0051] A high-performance tungsten-copper composite material comprises the following raw materials in parts by weight: 79.5 parts of tungsten powder, 18 parts of copper powder, and 2.5 parts of multi-walled carbon nanotubes.
[0052] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the preparation method of the modified carbon nanotubes in Comparative Example 2 is different from that in Example 1, and the other aspects are the same.
[0053] The modified carbon nanotubes are carbon nanotubes with lanthanum and nickel loaded on the surface, and the preparation method of the modified carbon nanotubes is as follows: (1) dispersing multi-walled carbon nanotubes and a 30% by mass hydrochloric acid solution at a speed of 500 rpm to obtain a carbon nanotube dispersion; the mass ratio of the multi-walled carbon nanotubes, the hydrofluoric acid solution, and the nitric acid solution is 1:5; (2) adding dodecylphenol polyoxyethylene ether to the carbon nanotube dispersion and stirring at a speed of 500 rpm to obtain a precursor solution; the mass ratio of dodecylphenol polyoxyethylene ether to the carbon nanotube dispersion is 0.01:1; (3) adding lanthanum sulfate, nickel sulfate, sodium dodecylbenzene sulfonate, and sodium sulfite into water and dispersing them evenly to obtain a loading liquid; the mass ratio of the lanthanum sulfate, nickel sulfate, sodium dodecylbenzene sulfonate, sodium sulfite, and water is 1:1:0.02:0.06:5; (4) Dropping the loading liquid into the precursor liquid, the mass ratio of the loading liquid to the precursor liquid is 0.15:1; adjusting the pH to 8.5 with sodium hydroxide, ultrasonically treating at 600 W for 30 min, and drying to obtain a precursor; placing the precursor in a tubular furnace, and heat treating at 150° C. for 1 h in an oxygen atmosphere to obtain modified carbon nanotubes.
[0054] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that the preparation method of the modified carbon nanotubes in Comparative Example 3 is different from that in Example 1, and the other aspects are the same.
[0055] The modified carbon nanotubes are carbon nanotubes with lanthanum loaded on the surface, and the preparation method of the modified carbon nanotubes is as follows: (1) adding multi-walled carbon nanotubes and a 35% by mass hydrofluoric acid solution into a 65% by mass nitric acid solution, and dispersing them uniformly at a speed of 500 rpm to obtain a carbon nanotube dispersion; the mass ratio of the multi-walled carbon nanotubes, the hydrofluoric acid solution, and the nitric acid solution is 1:1:4; (2) adding dodecylphenol polyoxyethylene ether to the carbon nanotube dispersion and stirring at a speed of 500 rpm to obtain a precursor solution; the mass ratio of dodecylphenol polyoxyethylene ether to the carbon nanotube dispersion is 0.01:1; (3) adding lanthanum sulfate, sodium dodecylbenzene sulfonate and sodium sulfite into water and dispersing them evenly to obtain a loading liquid; the mass ratio of the lanthanum sulfate, nickel sulfate, sodium dodecylbenzene sulfonate, sodium sulfite and water is 1:1:0.02:0.06:5; (4) Dropping the loading liquid into the precursor liquid, the mass ratio of the loading liquid to the precursor liquid is 0.15:1; adjusting the pH to 8.5 with sodium hydroxide, ultrasonically treating at 600 W for 30 min, and drying to obtain a precursor; placing the precursor in a tubular furnace, and heat treating at 150° C. for 1 h in an oxygen atmosphere to obtain modified carbon nanotubes.
[0056] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that the preparation method of the modified carbon nanotubes in Comparative Example 4 is different from that in Example 1, and the other aspects are the same.
[0057] The modified carbon nanotubes are carbon nanotubes with nickel loaded on the surface, and the preparation method of the modified carbon nanotubes is as follows: (1) adding multi-walled carbon nanotubes and a 35% by mass hydrofluoric acid solution into a 65% by mass nitric acid solution, and dispersing them uniformly at a speed of 500 rpm to obtain a carbon nanotube dispersion; the mass ratio of the multi-walled carbon nanotubes, the hydrofluoric acid solution, and the nitric acid solution is 1:1:4; (2) adding dodecylphenol polyoxyethylene ether to the carbon nanotube dispersion and stirring at a speed of 500 rpm to obtain a precursor solution; the mass ratio of dodecylphenol polyoxyethylene ether to the carbon nanotube dispersion is 0.01:1; (3) adding nickel sulfate, sodium dodecylbenzene sulfonate, and sodium sulfite into water and dispersing them evenly to obtain a loading liquid; the mass ratio of the lanthanum sulfate, nickel sulfate, sodium dodecylbenzene sulfonate, sodium sulfite, and water is 1:1:0.02:0.06:5; (4) Dropping the loading liquid into the precursor liquid, the mass ratio of the loading liquid to the precursor liquid is 0.15:1; adjusting the pH to 8.5 with sodium hydroxide, ultrasonically treating at 600 W for 30 min, and drying to obtain a precursor; placing the precursor in a tubular furnace, and heat treating at 150° C. for 1 h in an oxygen atmosphere to obtain modified carbon nanotubes.
[0058] Comparative Example 5 The difference between Comparative Example 5 and Example 1 is that the preparation method of the modified carbon nanotubes in Comparative Example 5 is different from that in Example 1, and the other aspects are the same.
[0059] The modified carbon nanotubes are carbon nanotubes with copper and nickel loaded on the surface, and the preparation method of the modified carbon nanotubes is as follows: (1) adding multi-walled carbon nanotubes and a 35% by mass hydrofluoric acid solution into a 65% by mass nitric acid solution, and dispersing them uniformly at a speed of 500 rpm to obtain a carbon nanotube dispersion; the mass ratio of the multi-walled carbon nanotubes, the hydrofluoric acid solution, and the nitric acid solution is 1:1:4; (2) adding dodecylphenol polyoxyethylene ether to the carbon nanotube dispersion and stirring at a speed of 500 rpm to obtain a precursor solution; the mass ratio of dodecylphenol polyoxyethylene ether to the carbon nanotube dispersion is 0.01:1; (3) adding copper sulfate, nickel sulfate, sodium dodecylbenzene sulfonate, and sodium sulfite into water and dispersing them evenly to obtain a loading liquid; the mass ratio of the copper sulfate, nickel sulfate, sodium dodecylbenzene sulfonate, sodium sulfite, and water is 1:1:0.02:0.06:5; (4) Dropping the loading liquid into the precursor liquid, the mass ratio of the loading liquid to the precursor liquid is 0.15:1; adjusting the pH to 8.5 with sodium hydroxide, ultrasonically treating at 600 W for 30 min, and drying to obtain a precursor; placing the precursor in a tubular furnace, and heat treating at 150° C. for 1 h in an oxygen atmosphere to obtain modified carbon nanotubes.
[0060] Comparative Example 6 The difference between Comparative Example 6 and Example 1 is that the preparation method of the modified carbon nanotubes in Comparative Example 6 is different from that in Example 1, and the other aspects are the same.
[0061] The modified carbon nanotubes are carbon nanotubes with lanthanum and nickel loaded on the surface, and the preparation method of the modified carbon nanotubes is as follows: (1) adding multi-walled carbon nanotubes and a 35% by mass hydrofluoric acid solution into a 65% by mass nitric acid solution, and dispersing them uniformly at a speed of 500 rpm to obtain a carbon nanotube dispersion; the mass ratio of the multi-walled carbon nanotubes, the hydrofluoric acid solution, and the nitric acid solution is 1:1:4; (2) adding lanthanum sulfate, nickel sulfate and sodium sulfite into water and dispersing them evenly to obtain a loading liquid; the mass ratio of the lanthanum sulfate, nickel sulfate, sodium dodecylbenzene sulfonate, sodium sulfite and water is 1:1:0.02:0.06:5; (3) Dropping a loading liquid into a nanotube dispersion liquid, wherein the mass ratio of the loading liquid to the nanotube dispersion liquid is 0.15:1; adjusting the pH to 8.5 with sodium hydroxide, ultrasonically treating the mixture at 600 W for 30 min, and drying the mixture to obtain a precursor; placing the precursor in a tubular furnace, and heat treating the precursor at 150° C. for 1 h in an oxygen atmosphere to obtain modified carbon nanotubes.
[0062] Comparative Example 7 The difference between Comparative Example 7 and Example 1 is that Comparative Example 7 uses an equal amount of modified graphene to replace the modified carbon nanotubes, and the other aspects are the same.
[0063] The preparation method of the modified graphene is: (1) adding graphene and a 35% by mass hydrofluoric acid solution into a 65% by mass nitric acid solution, and dispersing the mixture uniformly at a speed of 500 rpm to obtain a graphene dispersion; the mass ratio of the multi-walled carbon nanotubes, the hydrofluoric acid solution, and the nitric acid solution is 1:1:4; (2) adding dodecylphenol polyoxyethylene ether to the graphene dispersion and stirring at a speed of 500 rpm to obtain a precursor solution; the mass ratio of the dodecylphenol polyoxyethylene ether to the carbon nanotube dispersion is 0.01:1; (3) adding lanthanum sulfate, nickel sulfate, sodium dodecylbenzene sulfonate, and sodium sulfite into water and dispersing them evenly to obtain a loading liquid; the mass ratio of the lanthanum sulfate, nickel sulfate, sodium dodecylbenzene sulfonate, sodium sulfite, and water is 1:1:0.02:0.06:5; (4) dropping a loading liquid into a precursor liquid, wherein the mass ratio of the loading liquid to the precursor liquid is 0.15:1; adjusting the pH to 8.5 with sodium hydroxide, ultrasonically treating the mixture at 600 W for 30 min, and drying the mixture to obtain a precursor; placing the precursor in a tube furnace, and heat treating the precursor at 150 ° C for 1 h in an oxygen atmosphere to obtain modified graphene.
[0064] Performance Testing The properties of the embodiments and comparative examples are shown in Table 1.
[0065] Table 1
[0066] It can be seen from Table 1 that the tungsten-copper composite material of the present invention has excellent electrical conductivity and mechanical properties.
[0067] By comparing Example 1 with Comparative Examples 1 to 7, it can be seen that the modified carbon nanotubes described in the present invention significantly improve the electrical conductivity and mechanical properties of the composite material, and the modified carbon nanotubes prepared by different methods have different degrees of improvement in electrical conductivity and mechanical properties. The modified carbon nanotubes prepared by the preparation method of the present invention can more significantly improve the electrical conductivity and mechanical properties compared to other methods.
[0068] Finally, it should be noted that the above embodiments are intended to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A high performance tungsten copper composite material, characterized in that: The method comprises the following raw materials in parts by weight: 78.5 to 82 parts of tungsten powder, 15 to 20 parts of copper powder, and 1.5 to 3 parts of modified carbon nanotubes; The modified carbon nanotubes are carbon nanotubes with lanthanum and nickel loaded on the surface.
2. The high performance tungsten-copper composite material according to claim 1, characterized in that: The preparation method of the modified carbon nanotubes is: (1) adding multi-walled carbon nanotubes and hydrofluoric acid solution into nitric acid solution and dispersing them evenly to obtain a carbon nanotube dispersion; (2) adding dodecylphenol polyoxyethylene ether into the carbon nanotube dispersion and stirring evenly to obtain a precursor solution; (3) adding lanthanum sulfate, nickel sulfate, sodium dodecylbenzene sulfonate and a reducing agent into water and dispersing them evenly to obtain a loading liquid; (4) Dropping the loading liquid into the precursor liquid, adjusting the pH to 8.2-8.6, ultrasonically treating, and drying to obtain a precursor, and heat-treating the precursor in an oxygen atmosphere to obtain modified carbon nanotubes.
3. The high performance tungsten-copper composite material according to claim 2, characterized in that: The multi-walled carbon nanotubes have a diameter of 8-15 nm, a length of 30-50 μm, and a specific surface area of 210-250 m 2 / g; and / or The reducing agent is sodium sulfite.
4. The high performance tungsten-copper composite material according to claim 2, characterized in that: The mass fraction of the hydrofluoric acid solution is 30-40%; and / or The mass fraction of the nitric acid solution is 60-70%.
5. The high performance tungsten-copper composite material according to claim 2, characterized in that: The mass ratio of the multi-walled carbon nanotubes, the hydrofluoric acid solution and the nitric acid solution is 1: (0.5-1.2): (2-5); and / or The mass ratio of the dodecylphenol polyoxyethylene ether to the carbon nanotube dispersion is (0.005-0.02):
1.
6. The high performance tungsten-copper composite material according to claim 2, characterized in that: The mass ratio of the lanthanum sulfate, nickel sulfate, sodium dodecylbenzene sulfonate, reducing agent and water is 1: (0.8-1.2): (0.01-0.03): (0.05-0.08): (4-10); and / or The mass ratio of the load liquid to the precursor liquid is (0.08~0.2):
1.
7. The high performance tungsten-copper composite material according to claim 2, characterized in that: The temperature of the heat treatment is 120-160° C., and the time of the heat treatment is 0.5-2 h.
8. The high performance tungsten-copper composite material according to claim 1, characterized in that: The tungsten powder includes a first tungsten powder and a second tungsten powder, and the mass ratio of the first tungsten powder to the second tungsten powder is (2-5):1; the average particle size of the first tungsten powder is 2-5 μm, and the average particle size of the second tungsten powder is 0.1-0.2 μm.
9. The high performance tungsten-copper composite material according to claim 1, characterized in that: The average particle size of the copper powder is 2-10 μm.
10. The method for preparing the high-performance tungsten-copper composite material according to any one of claims 1 to 9, characterized in that: The following steps are involved: The tungsten powder, copper powder and modified carbon nanotubes are ball-milled and mixed evenly to obtain a mixed powder, and the mixed powder is pressed and sintered to obtain a high-performance tungsten-copper composite material; The green compact has a pressure of 180-220 MPa and a holding time of 2-5 min; The sintering temperature is 1050-1120° C., and the sintering time is 2-5 hours.